Context matters: how relative representation shapes Black and Latiné adolescents' perceptions of school ethnic climate and discrimination - Saafir, Amirah; Morales-Chicas, Jessica; Kogachi, Kara; Graham, Sandra (Frontiers in Education, 2025)
IntroductionThe current study used path analysis to examine Black and Latiné students' experiences with discrimination at school as a function of relative representation and perceptions of the school ethnic climate.MethodParticipants included 2,063 United States eighth graders (51% female; M = 13.33 years) who self-identified as Black (24%) or Latiné (76%).ResultsResults indicated that relative representation significantly predicted perceptions of the school ethnic climate such that, overrepresentation in class compared to the broader school context was associated with less favorable perceptions of the school ethnic climate, as measured by teacher support norms around diversity (b = −0.42, p < 0.001). In turn, less positive perceptions of teacher support norms predicted greater perceived discrimination from both adults (b = −0.78, p < 0.001) and peers (b = −0.35, p < 0.001).DiscussionThese findings highlight the importance of considering relative representation and underscore the critical role of teachers in fostering classroom environments that support ethnic and racial diversity and reduce discriminatory experiences for Black and Latiné youth.